The Analysis of Pronunciation Errors: Students’ Reading Aloud - Dinar Tia Sundari; Muhammad Anjar Nugraha; Sunara Sunara (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2023)
Students make pronunciation errors when they speak English considering English is not their first language. The research aimed to find out students pronunciation errors based on the pronunciation features, and students’ perspectives on English pronunciation. The research used 18 students as the sample that were then divided into 3 groups (high, medium, low). The research is a descriptive qualitative research that used an oral test and questionnaire to collect the data. A descriptive text was used in the research and students were asked to read aloud the text and it was voice recorded by the researcher to analyze students’ pronunciation errors. The researcher used a yes-or-no styled questionnaire to find out students’ perspectives on English pronunciation. The result of the research, particularly in the oral test shows that most common errors that students made are consonants and vowels as students made 44 consonant errors and 62 vowel errors in total. Whereas the result of the questionnaire shows that 94.5% of students think that English pronunciation is difficult and that they are unfamiliar with it. Moreover, motivation, confidence, and lack of practice are some factors that influence their English pronunciation.